Investigation of the thermal decomposition of poly(2-hydroxypropyl methacrylate) - Demirelli, K; Coskun, MF; Kaya, E; Coskun, M (Elsevier Sci Ltd, 2002)
2-Hydroxypropyl methacrylate (HPMA) was polymerized in the presence of AIBN at 60 degreesC. The thermal degradation behaviour of poly(HPMA) has been studied using thermogravimetry (TG), the IR examination of the partially degraded polymer, and a single line vacuum system consisting of a degradation tube, with a condenser for product collection and a gas phase IR cell. The cold ring fraction (CRF) was collected at two different temperatures, one of them (CRF1) is from ambient temperature to 340 degreesC and the other (CRF2) in the range 340-450 degreesC. The volatile products of the degradation were trapped at -196 degreesC (in liquid nitrogen). All fractions of the degradation were investigated by means of IR, H-1- and C-13-NMR techniques and the CRFs were also characterized by GC-MS. As major products of the degradation, the monomer, 2-propanal, methacrylic acid, 1,2-propandiol, 2-(2-propenyloxy) propyl methacrylate, 2-hydroxpropanal, and hydroxymethyl isopropyl ether were detected. Degradation mechanism and the origins of the identified products are discussed. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: thermal degradation; HPMA